An Assessment of the Ecosystem for Social Entrepreneurism in Alabama's Black Belt - Forbus, Robert; Snyder, Jason L. (Alabama State University, Center for Leardership and Public Policy, 2012)
Keywords: Alabama; Alabama; Entrepreneurship; Ecosystem health; dept.mkt; faculty_collection

Switching costs: A key to understanding and managing business consulting relationship longevity - Prince, M.; Everett, R.F. (Adv. Bus. Mark. Purch., 2012)
In consultant-client relationships, relationship longevity can create significant cost advantages and operational efficiencies for both client and consultant. At the same time, each party may also be motivated to look for new perspectives and opportunities by switching to new relationships. However, the benefits of replacing one consulting relationship with another are mitigated by switching costs: the costs associated with the act of changing the relationship itself. This chapter explores the concept of switching costs by examining various types of costs, the ways these costs have been conceptualized in the literature, and how these costs may impact the nature and continuity of consultant-client relationships. The chapter will end with a series of hypotheses and suggestions for a research agenda to further develop our understanding of this important phenomenon. Copyright © 2012 by Emerald Group Publishing Limited.
Journal Abbreviation: Adv. Bus. Mark. Purch.
Keywords: dept.mkt

Leading Edge Marketing Research: 21st-Century Tools and Practices - Kaden, Robert J.; Linda, Gerald; Prince, Melvin (SAGE Publications, 2012)
This book explores new and leading edge marketing research approaches as successfully practiced by visionaries of academia and the research industry. Ideal as either a supplementary text for students or as a guidebook for practitioners, this book showcases the excitement of a field where discoveries abound and researchers are valued for solving weighty problems and minimizing risks. The authors offer rich new tools to measure and analyze consumer attitudes, combined with existing databases, online bulletin boards, social media, neuroscience, radio frequency identification (RFID) tags, behavioral economics, and more. The reader will profit from the numerous contemporary case studies that demonstrate the key role of marketing research in corporate decision-making.
Keywords: Business & Economics / Marketing / Research; Marketing research; dept.mkt; faculty_collection

Consumer Cosmopolitanism in the Age of Globalization - Prince, Melvin (Business Expert Press, 2012)
Cosmopolitans are individuals with a distinctive kind of extended national and international orientation, a global vision, and sense of belonging to the world. These people are sophisticated and importantly engaged in the cultures outside of local geographical boundaries. But what do we know about them as consumers—their origins, values, media usage, and buyer behavior? This unique book details much about this group, and fills a knowledge gap that has long been overlooked largely because other related marketing areas have overshadowed and overlooked the notion of cosmopolitan consumers. Until this book, in fact, there has been no single authoritative source that directly and comprehensively covers the field of consumer cosmopolitanism. This book also includes original essays by an all-star cast of contributors, giving you an introduction to a powerful new approach to marketing, eclectically packed with novel ideas and insights that noticeably advance the marketing field and bring it more fully into the age of globalization.
Keywords: Business & Economics / Consumer Behavior; Consumer behavior; dept.mkt; faculty_collection

Attendance policies, student attendance, and instructor verbal aggressiveness - Snyder, Jason L; Forbus, Robert; Cistulli, Mark D (The Journal of Education for Business, 2012)
The authors utilized an experimental design across six sections of a managerial communications course (N = 173) to test the impact of instructor verbal aggressiveness and class attendance policies on student class attendance. The experimental group received a policy based on the principle of social proof (R. B. Cialdini, 2001), which indicated that for similar students, class attendance was linked to high academic performance. Students also assessed their instructor's level of verbal aggressiveness (D. A. Infante, 1979). Results suggest that instructor verbal aggressiveness did not influence class attendance. However, social proof did positively influence class attendance rates under certain circumstances. The authors discuss the study implications. © 2012, Copyright Taylor & Francis Group, LLC.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-116-818-454-801 tex.type: [object Object]
Keywords: attendance; dept.mkt; policy; social proof; verbal aggressiveness